Prophetic Approach Towards Personality Development And Its Significance In Modern Educational Context - Dr. Riaz Ahmad Saeed, (Seerat Studies, 2023)
Personality development means, to enhance mental and physical capacity of a person for better professional performance and leadership but Islam correlates it with moral development as well, which is more likely to be known as character building. It is observed that different philosophical, political, social and educational experts have tried their best for an ideal personality development in different eras of the human history. The prophetic methodology is considered most significant strategy for personality development and character-building. The Holy Prophet (ﷺ) initiated many bold steps to develop the character of his companions on Islamic foundations. It was very difficult task, but the Messenger of Allah (ﷺ) succeeded to transform them according to divine vision in few years. Modern educational context has lack of this aspect of personality development with special reference to moral and physical development. Here a question arises if the beloved Prophet (ﷺ) can produce best men power with his kind efforts and unique approaches then how we can use these approaches in modern era. The core objective of this study is to discover the approaches and techniques of the Holy Prophet (ﷺ) about personality development and character-building. It also mentions the need and importance of personality development in modern Muslim educational discourse. In this research work analytical approach has been adopted with qualitative research methodology. This study concludes if we adopt the Prophet’s (ﷺ) active approach and techniques for personality development we can produce better professionals and academicians.